New data on some crickets of the subfamilies Landrevinae, Phaloriinae and Podoscirtinae (Orthoptera: Grylloidea) from Laguna (Philippines: Luzon Island) - Tan, Ming Kai; Gorochov, Andrei V.; Baroga-Barbecho, Jessica B.; Yap, Sheryl A. (Zootaxa, 2020)
Recent orthopteran sampling at Laguna in Luzon Island of the Philippines revealed noteworthy crickets from the subfamilies Landrevinae, Phaloriinae and Podoscirtinae. We describe one species new to science from the subfamily Podoscirtinae: Mnesibulus laguna n. sp. We record new locality and complete the genitalia description of Phaloria (Phaloria) modulator (Saussure, 1878), previously described with incomplete parts of genitalia in the holotype. We also differentiate Duolandrevus (Jorama) curtipennis Chopard, 1937 from Laguna which varies slightly from the subspecies from Palawan and Mindoro.